Outcomes of Multidisciplinary Team Approach in Rehabilitation of Patients with Stroke - Shazia Kanwal, Riaz Hashmi, Wajida Perveen, Misbah Amanat Ali, M. Akhtar, Arooj Munawar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find the benefits of the multidisciplinary team approach for the rehabilitation of patients with stroke. Methodology: This cohort case series was conducted at physiotherapy department, Syed Medical Complex Sialkot in 2017-18 after ethical approval. Open epi calculator was used for sample size estimation and found 70 patients. Non-probability, consecutive sampling technique was used to enroll the patients after screening for eligibility criteria and taking their consent. FIMFAM scale was used to measure the outcomes at 1st visit, after 4 weeks, and on follow up. Results: Mean ± standard deviation of the age of participants was 62.57±8.02 years. Out of them, 74.28% (52) had left sided while 25.71% (18) had right sided stroke. Mean of total FIMFAM score at 1st visit, after 4 weeks, and on follow up was 42.50±20.58, 77.70±25.56 and 126.83±21.30 respectively (P=0.000). Mean difference of 1st visit and after 4 weeks was 35.20 (p value=0.000), Mean difference after 4 weeks and follow up was 49.13 (p value=0.000). Conclusion: We concluded that multidisciplinary team approach in patients with stroke can produce significant improvement in their functional outcomes, therefore can limit the risk of death and delayed recovery.